STRATEGI PEMBELAJARAN DALAM KETERAMPILAN BERBICARA DI SEKOLAH DASAR - Ni Putu Suparmini; Ni Putu Adi Utami; Dewa Made Riyan Gunawan; I Wayan Dio Sepliawan; Ida Bagus Putrayasa; I Nyoman Sudiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Speaking skills are one of the important aspects in developing students' language skills, especially at the elementary school level. Learning speaking skills is not only aimed at training oral communication skills, but also at forming students' courage, self-confidence, and critical thinking skills. This study aims to identify and analyze learning strategies used by teachers in developing speaking skills in elementary schools. This study uses a qualitative approach with a case study method implemented at SD No. 4 Tuban. Data collection techniques include observation, interviews, and documentation. The results of the study showed that the strategies used included storytelling activities, role-playing, group discussions, and open questions and answers. Although these strategies are effective in encouraging active student participation, there are obstacles such as low student self-confidence, limited learning media, and less than optimal assessment of speaking skills. Therefore, it is necessary to develop more varied methods, supporting learning media, and a structured evaluation system so that learning speaking skills in elementary schools can run more effectively.